Structural validation and cross-cultural robustness of the European Cyberbullying Intervention Project Questionnaire. (September 2015) - Del Rey, Rosario; Casas, José A.; Ortega-Ruiz, Rosario; Schultze-Krumbholz, Anja; Scheithauer, Herbert; Smith, Peter; Thompson, Fran; Barkoukis, Vassilis; Tsorbatzoudis, Haralambos; Brighi, Antonella; Guarini, Annalisa; Pyżalski, Jacek; et al.
Highlights: Cyberbullying is a dynamic relationship between the aggressor and the victim. Establishing the prevalence of cyberbullying is difficult due to the instruments used. The instrument validated integrates the traditional bullying characteristics. Differences in prevalence of cyberbullying among countries using a single instrument. Abstract: During the last decade, cyberbullying has become an increasing concern which has been addressed by diverse theoretical and methodological approaches. As a result there is a debate about its nature and rigorously validated assessment instruments have not yet been validated. In this context, in the present study an instrument composed of 22 items representing the different types of behaviours and actions that define cyberbullying has been structurally validated and its cross-cultural robustness has been calculated for the two main dimensions: cyber-victimization and cyber-aggression. To this end, 5679 secondary school students from six European countries (Spain, Germany, Italy, Poland, United Kingdom, and Greece) were surveyed through this self-report questionnaire which was designed based on previously existing instruments and the most relevant conceptual elements. Exploratory and confirmatory factor analyses were conducted and the global internal consistency was computed for the instrument and its two dimensions. Identical factor structures were found across all of the six subsamples. The results contribute to existing research by providing an instrument, the European Cyberbullying Intervention Project Questionnaire, which has been structurally validated in a wide sample from six different countries and that is useful to evaluate psycho-educative interventions against cyberbullying.